Interleukin-8 expression in Helicobacter pylori infected, normal, and neoplastic gastroduodenal mucosa. Issue 1 (January 1994) - Crabtree, J E; Wyatt, J I; Trejdosiewicz, L K; Peichl, P; Nichols, P H; Ramsay, N; Primrose, J N; Lindley, I J
Abstract : AIMS--To investigate the expression of interleukin-8 (IL-8) in Helicobacter pylori infected normal and neoplastic gastroduodenal mucosa, and in established gastric cancer cell lines. METHODS--Immunofluorescence techniques were used to localise IL-8 in cryosections of gastric (n = 25) and duodenal (n = 17) endoscopic biopsy specimens an in resected gastric tumour tissue samples from 16 patients. Two gastric cancer cell lines (Kato 3 and MKN 45) were examined for IL-8 protein expression by immunofluorescence and for the presence of IL-8 mRNA by reverse transcription followed by the polymerase chain reaction (RT-PCR). RESULTS--IL-8 was localised to the epithelium in histologically normal gastric mucosa, with particularly strong expression in the surface cells. IL-8 expression was also a feature of surface epithelium in the duodenal bulb, but was much reduced in the second part of the duodenum. In chronic H pylori-associated gastritis gastritis gastric epithelial IL-8 expression was increased and expression of IL-8 within the lamina propria was evident. By contrast, large areas of IL-8 negative epithelium were observed in the body mucosa of a subject with Ménétrier's disease. In gastric carcinoma the tumour cells were positive for IL-8. IL-8 was also detected by immunofluorescence in unstimulated Kato 3 and MKN 45 cells, and constitutive IL-8 gene expression in these cell lines was confirmed by detection of IL-8 mRNA by RT-PCR. CONCLUSIONS--Immunoreactive IL-8, a potent neutrophil chemotactic and activating factor, is present in the epithelium of both normal and inflamed gastric mucosa with increased expression in the latter. There is site dependent variation in epithelial IL-8 expression within the gastroduodenal mucosa. The expression of the pro-inflammatory cytokine IL-8 in gastric carcinoma cells may influence peritumoural cellular infiltrates.